The Juridical Analysis of Criminal Acts on Negligence of Traffic Accidents that Cause Death - Fitri Ida Laela (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
This study aims to explain the problem, which is the basis or consideration of the judge in considering the elements of the criminal act of negligence in traffic accidents that result in the loss of other people's lives. This study is a literature study with a normative juridical approach. The data collection technique used in this research is the documentation technique. At the same time, the analysis technique used in this research is descriptive. The findings in this study are that the judge's considerations in determining criminal sanctions against perpetrators of criminal acts of negligence in traffic accidents are divided into two, namely, juridical considerations and non-juridical considerations. A judge gives juridical considerations to a case based on statutory regulations, indictments, and demands from the public prosecutor. The judge's consideration is also based on the facts found in the trial examination based on the evidence submitted. At the same time, non-juridical considerations include the judge's consideration of the factors that will burden the crime and the factors that relieve the perpetrators of the crime.